GAMING SMARTPHONE’S BRAND PERSONALITY: AN EMPIRICAL STUDY OF BLACK SHARK SMARTPHONE IN INDONESIA - Manurung, MM, Siska Purnama; Febridiansyah, Zaky (FIRM Journal of Management Studies, 2023)
This study aims to investigate the impact of brand personality, product quality, price, and online promotion on customer loyalty towards the Black Shark gaming smartphone. Data was collected through questionnaires, employing a quantitative research methodology. Statistical analysis was conducted using SPSS software. The target population consisted of individuals who have used the Black Shark gaming smartphone. Non-probability purposive sampling was employed, and a total of 111 respondents participated in the study, representing an unknown population in Indonesia. Multiple linear regression analysis was employed to examine the relationship between the dependent variable and two or more independent variables. The findings indicate that product quality and online promotion do not have a significant influence on customer loyalty. However, brand personality and price were found to have a significant impact on customer loyalty towards the Black Shark gaming smartphone. Additionally, the study revealed that brand personality, product quality, price, and online promotion collectively influence customer loyalty towards the Black Shark gaming smartphone. Consequently, by enhancing brand personality, improving product quality, maintaining competitive pricing, and intensifying online promotion, companies can effectively enhance customer loyalty towards the Black Shark gaming smartphone.